Micro-CT examination of human bone: from biopsies towards the entire organ - Egon Perilli (Annali dell'Istituto Superiore di Sanità, 2012)
Micro-CT systems are available that facilitate ex vivo examinations of human specimens as big as entire vertebrae, with spatial resolutions in the 10-micrometer range. This opens a new way for looking at entire bones in 3D. Accurate description of the internal microarchitecture of the entire organ can be obtained, at spatial resolutions previously achievable only on excised biopsies. These high resolution scans produce large datasets and come with costs and benefits, which have to be considered in the successful planning of an experiment. The aim of this paper is to present examples of human vertebrae scanned at high resolution (17 μm/pixel), allowing the visualization and quantification of the microarchitecture, and to discuss some aspects of using high resolution scans of such large specimens. The datasets were down-sampled to 34 μm and 68 μm pixel size, and their morphometric parameters compared to those obtained at 17 μm pixel size, in relation to data size and calculation time.